Carbon economy of skeletal muscle growth: Warburg-like metabolic remodeling drives lean accretion and shapes meat quality - C.N. Yen; M.D. Zumbaugh; J.C. Wicks; M. Beline; J.S. Bodmer; E.C. Roth; L.A. Rimmer; A. Wivell; S.D. Gerrard; S.L. Silva; S.K. Matarneh; D.E. Gerrard (Meat Science, 2026)

Beef carcass electrical stimulation enhances Calpain-1 autolysis but not proteolysis - J.S. Bodmer; M. Beline; C.N. Yen; E.C. Roth; M. Koohmaraie; T.H. Shi; S.L. Silva; D.E. Gerrard (Meat Science, 2026)

Act fast: improved control of Rhamnus cathartica with rapid foliar herbicide and herbaceous seeding - Andrew D. Kaul; Peter D. Wragg; Peter B. Reich; Alex M. Roth; Paul J. Bockenstedt; Michael J. Schuster (Forest Ecology and Management, 2026)

Management practices shape soil fungal diversity and functional traits in Swiss forests - Xingguo Han; Fabienne Kuhn; Flurin Leugger; Thibault Lachat; Nicolas Roth; Martin M. Gossner; Loïc Pellissier; Aline Frossard (European Journal of Soil Biology, 2026)

Corrigendum to “Carbon economy of skeletal muscle growth: Warburg-like metabolic remodeling drives lean accretion and shapes meat quality” [Meat Sci. 242 (2026) 110181] - C.N. Yen; M.D. Zumbaugh; J.C. Wicks; M. Beline; J.S. Bodmer; E.C. Roth; L.A. Rimmer; A. Wivell; S.D. Gerrard; S.L. Silva; S.K. Matarneh; D.E. Gerrard (Meat Science, 2026)

Calcium and calpastatin delay proteolysis early during beef maturation - J.S. Bodmer; M. Beline; C.N. Yen; M. Zumbaugh; J.C. Wicks; E.C. Roth; J. Chen; M. Koohmaraie; S. Matarneh; T.H. Shi; S.L. Silva; D.E. Gerrard (Meat Science, 2026)

Differential motor unit firing rate and hypertrophic adaptations of the vastus lateralis despite similar strength increases following high-load versus combined high- and low-load resistance training interventions - Alex A. Olmos; Daniel J. Lawson; Stephanie A. Sontag; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Allen L. Redinger; Sean M. Gamache; Michael A. Trevino (Experimental Brain Research, 2026)

Nasal hormone administration can support ambystomid salamander ex situ conservation breeding programs - Devin M. Chen; Carrie K. Kouba; Terri L. Roth; Peter J. Allen; Nucharin Songsasen; Andrew J. Kouba (Journal for Nature Conservation, 2026)

The opsin repertoire of syngnathids (pipefish & seahorses) and its expression changes throughout development, season and between sexes in Syngnathus typhle - Theresa Pöpperl; Emely Burmeister; Arseny Dubin; Teresa-M. Schieberlein; Olivia Roth; Ralf F. Schneider (Hydrobiologia, 2026)
Vision is an important sense for fish and, as various properties of the water column affect how well different light wavelengths are transmitted, fishes’ visual sensitivity spectra reflect the varying ambient light conditions across habitats. Syngnathids (pipefishes & seahorses) inhabit various salt- and freshwater habitats-many affected by geological, anthropogenic and seasonal changes, challenging these visual predators. Here, we explored their visual opsin gene repertoire and found that, while retaining most common visual opsin genes, syngnathids have lost the UV-sensitive SWS1, while the subfamily of Nerophinae likely evolved a second copy of RH2 and all seahorses lost SWS2b. We further tested if the widely distributed Syngnathus typhle shows flexibility in visual capabilities throughout development and across the breeding season in its habitat, the Baltic Sea. Adult opsin expression composition was established soon after birth, with SWS2b barely being expressed. Adults changed the composition of expressed opsins across seasons, likely in response to the changing sunlight intensity and food composition & availability. Being the choosier sex, males expressed more green-light sensitive RH2 than females, possibly improving their ability to assess mate quality. S. typhle therefore showed highly dynamic opsin expression, plastically responding to fluctuations in its specifically variable habitat.

Oh deer! Videography reveals a range of defensive behaviors against a cervid by a ground‐nesting bird - Kylie L. Brunette; Amber M. Roth; Rachel L. Darling; Michael L. Peters; Erik J. Blomberg (Ecology, 2026)

The effect of muscle oxygenation on neuromuscular efficiency and force complexity - Petra Kis; Colin W. Kipper; Kylie N. Burleson; Brenden L. Roth; Jerome Hausselle; Joshua L. Keller; Shane M. Hammer (European Journal of Applied Physiology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Aerosol Delivery of Polyelectrolyte Surfactant—Antimicrobial Nanoparticles to the Lungs - Yadiel Varela Soler; Amanda S. Padilla-López; Sughosha Rao; Leonardo Calderon; Gediminas Mainelis; Olga Garbuzenko; Tamara Minko; David I. Devore; Charles M. Roth (Pharmaceutical Research, 2026)
Background Lung infections affect over 80% of adults with cystic fibrosis, with Pseudomonas aeruginosa being a leading pathogen. Although antibiotics are frequently nebulized as standard treatments, the physicochemical environment of the diseased lung often limits their diffusion and overall effectiveness. Our previous studies showed polyelectrolyte surfactants (PS) to be a promising delivery system for cationic antimicrobials in vitro . This study seeks to expand that knowledge by evaluating their potential for nebulized delivery. Methods To achieve this, we evaluated their size and antimicrobial activity following nebulization; in vitro toxicity against epithelial cells and erythrocytes; and biodistribution and expression of inflammation markers following administration to healthy mice. Results The nanoparticle formulation exhibited a mucolytic effect on an artificial mucus model of cystic fibrosis mucus. Following nebulization, nanoparticles retained both their size and biological activity. Additionally, they displayed no observable toxicity in vitro against either human lung epithelial cells or erythrocytes; instead, epithelial cells treated with PS-based nanoparticles showed increased cell viability. Following administration of these formulations to mice via inhalation, over 70% of the recovered nanoparticles were retained in the lungs 24 h after treatment, with a small fraction being uniformly distributed to other tissues. A screen of key inflammatory cytokines revealed that inhalation treatment led to a slight increase of IL-6 in the liver and IL-18 in the spleen. These increases seem to be consistent with a minor inflammatory response. Conclusion Overall, the results suggest that PS are a promising nanotechnology for the pulmonary delivery of cationic drugs.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

Marine resources alter tundra food web dynamics by subsidizing a terrestrial predator on the sea ice - Sean M. Johnson‐Bice; Frank B. Baldwin; Evan S. Richardson; James D. Roth (Ecology, 2025)
Predator use of resource subsidies can strengthen top‐down effects on prey when predators respond numerically to subsidies. Although allochthonous subsidies are generally transported along natural gradients, consumers can cross ecosystem boundaries to acquire subsidies, thereby linking disparate ecosystems. In coastal Arctic ecosystems, terrestrial predators like Arctic foxes ( Vulpes lagopus ) cross into the marine environment (sea ice) during winter to access marine resources. Arctic foxes kill seal pups and scavenge seal carrion (often remains from polar bear Ursus maritimus kills), especially when rodent abundance is low. Terrestrial predator use of marine subsidies may strengthen the top‐down control of tundra food webs, but this hypothesis remained untested. We evaluated tundra food web dynamics at the terrestrial–marine interface from an ecosystem‐level perspective by assessing: (1) how winter environmental conditions affect rodent abundance and marine subsidy availability, (2) the response of the Arctic fox population to this seasonal food variability, and (3) the subsequent effects of Arctic foxes on Canada goose ( Branta canadensis interior ) reproduction. Arctic foxes responded numerically to rodent abundance, which was positively related to snow persistence. Arctic fox abundance was positively related to polar bear body condition metrics, which were used as a proxy for marine subsidy availability. Canada goose reproductive success, in turn, was negatively related to Arctic fox abundance. Long‐term trends in goose reproduction and snow persistence also indicate an ongoing phenological mismatch between nesting initiation and spring onset. Our results reveal near‐term apparent competition between rodents and geese through a shared predator, Arctic foxes, contrasting with prior studies evaluating rodent–goose–predator relationships. Moreover, we establish a link between tundra and sea ice food webs by demonstrating how seal availability can affect goose reproduction indirectly by increasing Arctic fox predation on goose nests via a population response of foxes to marine resources. These marine resources are often provisioned by polar bears, and with both Arctic foxes and polar bears undergoing long‐term regional declines evidently driven by climate‐related changes in prey abundance and availability, we contextualize our study within ongoing climate change and highlight the vulnerability of this likely widespread terrestrial–marine linkage in a warming Arctic.

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

Temperature dependent rate constants for the gas phase reactions of OH radical with first generation products of monoterpenes oxidation: nopinone, limononaldehyde, myrtenal and ketolimonene - M. Fakih; A. Abou-Dib; A. Chakir; E. Roth (Atmospheric Environment, 2025)

Development of diagnostic markers for the disease susceptibility gene Tsn1 in wheat reveals novel resistance alleles and a new locus required for ToxA sensitivity - Katherine L. D. Running; Krishna Acharya; Tiana M. Roth; Gurminder Singh; Agnes Szabo-Hever; Amanda R. Peters Haugrud; Jason D. Fiedler; Timothy L. Friesen; Justin D. Faris (Theoretical and Applied Genetics, 2025)

Click beetles (Elateridae) identify conservation units in Oriental and European beech forests - Giorgi Mamadashvili; Andrea Jarzabek-Müller; Hazan Alkan Akinci; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Diedus; Lars Drössler; Jamshid Eslamdoust; Kostadin B. Georgiev; Tigran Ghrejyan; et al. (Journal of Insect Conservation, 2025)
Beech trees form major parts of lowland temperate forests in the Western Palearctic. To protect biodiversity, many beech forests have been designated as World Heritage Sites or established as networks of beech forest reserves. However, the insect communities within these protected forests have not been well explored. In this study, elaterids (Elateridae, Coleoptera) in 26 beech forests, from France in the west to Iran in the east, were sample to identify conservation clusters and hotspots of biodiversity. Sampling was mostly carried out using window traps and all specimens were identified to the species level. A total of 118 species were identified including one previously unreported species. Community composition analyses that focused on rare species identified five clusters comprising distinct communities: (i) the Hyrcanian Forest in Iran, (ii) the Lesser Caucasus in Türkiye, Georgia and Armenia, (iii) the Greater Caucasus in Georgia, (iv) the Pyrenees and (v) a cluster made up of forests from Central Europe, the Balkan region and the Carpathians. After controlling for sampling effort (individuals), the highest richness was found in the Caucasus region. The proportion of endemics was highest in the Oriental beech forests of the Caucasus and in Hyrcanian forests. These findings highlight the unique biodiversity of beech forests and support calls for intensified conservation actions in beech forests, particularly in the Caucasus and Hyrcanian regions, which should be prioritized for conservation efforts, due to their unique fauna. Implications for insect conservation Our study underscores the importance of protecting beech forests, especially in the Caucasus and Hyrcanian regions, as they host unique and endemic insect species critical for biodiversity conservation.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

In vitro proteolysis mirrors intact muscle maturation in beef carcasses - J.S. Bodmer; M. Beline; C.N. Yen; J.C. Wicks; S.T. Amorim; E.C. Roth; F.H. Biase; M. Koohmaraie; S. Matarneh; T.H. Shi; S.L. Silva; D.E. Gerrard (Meat Science, 2025)

Revegetation of Elymus grasses suppresses invasive Rhamnus cathartica in deciduous forest understories - Michael J. Schuster; Peter D. Wragg; Alex M. Roth; Paul Bockenstedt; Lee Frelich; Peter B. Reich (Ecological Engineering, 2025)

Improving drone-based uncalibrated estimates of wheat canopy temperature in plot experiments by accounting for confounding factors in a multi-view analysis - Simon Treier; Juan M. Herrera; Andreas Hund; Norbert Kirchgessner; Helge Aasen; Achim Walter; Lukas Roth (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Exploring weight-related self-monitoring as a potential risk factor for eating disorder symptoms in adults – A systematic review and meta-analysis - Annika M. Roth; Judith R. Gruber; Andreas Reif; Martin Schultze; Silke Matura (Appetite, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Elucidating the redox-driven sodium pumping mechanism of the ancient Rnf complex - Hyunho Kim; Anuj Kumar; Patricia Saura; Jennifer Roth; Stefan Bohn; Tristan Reif-Trauttmansdorff; Anja Schubert; Volker Müller; Jan M. Schuller; Ville R.I. Kaila (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Modeling of micron-sized aluminum particle combustion in hot gas flow - S. Feng; Y. Qiu; S. Xu; Z. Wu; C. Ruan; A. Roth; E. Nilsson; E. Berrocal; Z.S. Li; M. Alden; X.S. Bai (Fuel, 2024)

Factors influencing detection of invasive Red Swamp Crayfish Procambarus clarkii (Girard, 1852) in Michigan ponds - William R. Budnick; Dan Hayes; Seth Herbst; Jeannette Kanefsky; Lucas Nathan; Brian M. Roth; Nicholas M. Sard; Kim T. Scribner; Kelley Smith; Sara Thomas (Hydrobiologia, 2024)

A Review of Viable Mineral Precipitates in Pit Lake Modeling - Andy Davis; M. Lengke; N. Sims; M. Roth (Mine Water and the Environment, 2024)

Suboptimal environmental conditions prolong phage epidemics in bacterial populations - Henry Goehlich; Olivia Roth; Michael Sieber; Cynthia M. Chibani; Anja Poehlein; Jelena Rajkov; Heiko Liesegang; Carolin C. Wendling (Molecular Ecology, 2024)
Infections by filamentous phages, which are usually nonlethal to the bacterial cells, influence bacterial fitness in various ways. While phage‐encoded accessory genes, for example virulence genes, can be highly beneficial, the production of viral particles is energetically costly and often reduces bacterial growth. Consequently, if costs outweigh benefits, bacteria evolve resistance, which can shorten phage epidemics. Abiotic conditions are known to influence the net‐fitness effect for infected bacteria. Their impact on the dynamics and trajectories of host resistance evolution, however, remains yet unknown. To address this, we experimentally evolved the bacterium Vibrio alginolyticus in the presence of a filamentous phage at three different salinity levels, that is (1) ambient, (2) 50% reduction and (3) fluctuations between reduced and ambient. In all three salinities, bacteria rapidly acquired resistance through super infection exclusion (SIE), whereby phage‐infected cells acquired immunity at the cost of reduced growth. Over time, SIE was gradually replaced by evolutionary fitter surface receptor mutants (SRM). This replacement was significantly faster at ambient and fluctuating conditions compared with the low saline environment. Our experimentally parameterized mathematical model explains that suboptimal environmental conditions, in which bacterial growth is slower, slow down phage resistance evolution ultimately prolonging phage epidemics. Our results may explain the high prevalence of filamentous phages in natural environments where bacteria are frequently exposed to suboptimal conditions and constantly shifting selections regimes. Thus, our future ocean may favour the emergence of phage‐born pathogenic bacteria and impose a greater risk for disease outbreaks, impacting not only marine animals but also humans.

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Use of satellite imagery to estimate distribution and abundance of Cumberland Sound beluga whales reveals frequent use of a glacial river estuary - Amanda M. Belanger; Bryanna A. H. Sherbo; James D. Roth; Cortney A. Watt (Frontiers in Marine Science, 2024)
Limiting disturbance in critical habitats is an important part of ensuring the well-being and sustainability of populations at risk, such as Cumberland Sound beluga whales ( Delphinapterus leucas ). Using non-disruptive Very High Resolution (VHR) satellite imagery, an emerging tool in cetacean monitoring, we aimed to estimate summer abundance and identify critical habitat for Cumberland Sound beluga whales. Specifically we looked in fiords that comprise their summer distribution, such as Clearwater Fiord where there is a large estuary, an important habitat to many beluga populations. Satellite images of the area were collected in 2020 and 2021, at 30 cm resolution, and in 2022 at 50 cm resolution. We evaluated beluga whale distribution using Kernel density, and identified critical habitats as areas consistently part of the beluga whale core distribution across years. Clearwater Fiord abundance estimates were corrected for whales that were too deep to be identified in the images. The estimates were significantly lower in 2021 (197 whales, 95%CI: 180-216) and 2022 (194 whales, 95%CI: 172-218) compared to 2020 (393 whales, 95%CI: 366-422). Other fiords were only imaged in 2021 and 2022, resulting in average corrected abundance estimates for all fiords of 462 (95% CI: 425-502) and 252 (95%CI: 226-280) beluga whales, respectively. Downsampling of 30 cm images to 50 cm resulted in up to 45% fewer whales detected. The only critical habitat identified within the summer distribution was in Clearwater Fiord, in or near the estuary freshwater plume and in a bay to the west of the plume. The identified critical habitats should be areas of consideration in the continued discussion on the protection and sustainability of the Cumberland Sound beluga whale population.

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

A Cosmic View of ‘Tundra Gardens’: Satellite Imagery Provides a Landscape-Scale Perspective of Arctic Fox Ecosystem Engineering - Sean M. Johnson-Bice; James D. Roth; John H. Markham (Ecosystems, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

No evidence of a long-lived seedbank in common buckthorn, Rhamnus cathartica L., within Minnesota deciduous forests - Michael J. Schuster; Peter D. Wragg; Alexander M. Roth; Peter B. Reich (Biological Invasions, 2023)

The manganese carbonyl complex [Mn(CO)3(tqa-κ3N)]Br: A novel antimicrobial agent with the potential to treat avian pathogenic Escherichia coli (APEC) infections - Jonathan W. Betts; Shaun Cawthraw; Joan A. Smyth; Robert K. Poole; Patrick Roth; Ulrich Schatzschneider; Roberto M. La Ragione (Veterinary Microbiology, 2023)

Drivers of tree-related microhabitat profiles in European and Oriental beech forests - Giorgi Mamadashvili; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Deidus; Lars Drössler; Céline Emberger; Kostadin B. Georgiev; Tigran Ghrejyan; Martin M. Gossner; Ruslan Hleb; et al. (Biological Conservation, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Ganymede's atmosphere as constrained by HST/STIS observations - F. Leblanc; L. Roth; J.Y. Chaufray; R. Modolo; M. Galand; N. Ivchenko; G. Carnielli; C. Baskevitch; A. Oza; A.L.E. Werner (Icarus, 2023)

Arctic and red fox population responses to climate and cryosphere changes at the Arctic’s edge - Jacqueline S. Verstege; Sean M. Johnson-Bice; James D. Roth (Oecologia, 2023)

Multiple sources implicated in the red swamp crayfish invasion in Michigan, USA - N. M. Sard; K. R. Smith; B. M. Roth; L. R. Nathan; S. J. Herbst; K. T. Scribner (Biological Invasions, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Experimental natural disturbance-based silviculture systems maintain mature forest bird assemblage long-term in Maine (USA) - Carl K. Pohlman; Amber M. Roth; Mitschka J. Hartley; Malcolm L. Hunter; Brian J. McGill; Robert S. Seymour (Forest Ecology and Management, 2023)

Demonstration of Reversible Dispersion in a Darcy-Scale Push-Pull Laboratory Experiment - Roseanna M. Neupauer; Eric J. Roth; John P. Crimaldi; David C. Mays; Lauren J. Sather (Transport in Porous Media, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Whisker spots on polar bears reveal increasing fluctuating asymmetry - Caila E. Kucheravy; Jane M. Waterman; James D. Roth (Mammalian Biology, 2022)

Spatial variation in predator communities, predation risk, and shorebird daily nest survival near a sub-Arctic human settlement - Taylor M. Brown; Victor Olek; James Roth; Laura McKinnon (Polar Biology, 2022)

A new benzophenone, and the antiplasmodial activities of the constituents of Securidaca longipedunculata fresen (Polygalaceae) - Douglas O. Ochora; Esezah Kakudidi; Jane Namukobe; Matthias Heydenreich; Paolo Coghi; Li Jun Yang; Edwin W. Mwakio; Ben Andagalu; Amanda Roth; Hoseah M. Akala; Vincent K. W. Wong; Abiy Yenesew (Natural Product Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Lean mass sparing in resistance-trained athletes during caloric restriction: the role of resistance training volume - C. Roth; B. J. Schoenfeld; M. Behringer (European Journal of Applied Physiology, 2022)
Many sports employ caloric restriction (CR) to reduce athletes’ body mass. During these phases, resistance training (RT) volume is often reduced to accommodate recovery demands. Since RT volume is a well-known anabolic stimulus, this review investigates whether a higher training volume helps to spare lean mass during CR. A total of 15 studies met inclusion criteria. The extracted data allowed calculation of total tonnage lifted (repetitions × sets × intensity load) or weekly sets per muscle group for only 4 of the 15 studies, with RT volume being highly dependent on the examined muscle group as well as weekly training frequency per muscle group. Studies involving high RT volume programs (≥ 10 weekly sets per muscle group) revealed low-to-no (mostly female) lean mass loss. Additionally, studies increasing RT volume during CR over time appeared to demonstrate no-to-low lean mass loss when compared to studies reducing RT volume. Since data regarding RT variables applied were incomplete in most of the included studies, evidence is insufficient to conclude that a higher RT volume is better suited to spare lean mass during CR, although data seem to favor higher volumes in female athletes during CR. Moreover, the data appear to suggest that increasing RT volume during CR over time might be more effective in ameliorating CR-induced atrophy in both male and female resistance-trained athletes when compared to studies reducing RT volume. The effects of CR on lean mass sparing seem to be mediated by training experience, pre-diet volume, and energy deficit, with, on average, women tending to spare more lean mass than men. Potential explanatory mechanisms for enhanced lean mass sparing include a preserved endocrine milieu as well as heightened anabolic signaling.

Combining population genomics with demographic analyses highlights habitat patchiness and larval dispersal as determinants of connectivity in coastal fish species - Halvor Knutsen; Diana Catarino; Lauren Rogers; Marte Sodeland; Morten Mattingsdal; Marlene Jahnke; Jeffrey A. Hutchings; Ida Mellerud; Sigurd H. Espeland; Kerstin Johanneson; Olivia Roth; Michael M. Hansen; et al. (Molecular Ecology, 2022)
Gene flow shapes spatial genetic structure and the potential for local adaptation. Among marine animals with nonmigratory adults, the presence or absence of a pelagic larval stage is thought to be a key determinant in shaping gene flow and the genetic structure of populations. In addition, the spatial distribution of suitable habitats is expected to influence the distribution of biological populations and their connectivity patterns. We used whole genome sequencing to study demographic history and reduced representation (double‐digest restriction associated DNA) sequencing data to analyse spatial genetic structure in broadnosed pipefish ( Syngnathus typhle ). Its main habitat is eelgrass beds, which are patchily distributed along the study area in southern Norway. Demographic connectivity among populations was inferred from long‐term (~30‐year) population counts that uncovered a rapid decline in spatial correlations in abundance with distance as short as ~2 km. These findings were contrasted with data for two other fish species that have a pelagic larval stage (corkwing wrasse, Symphodus melops ; black goby, Gobius niger ). For these latter species, we found wider spatial scales of connectivity and weaker genetic isolation‐by‐distance patterns, except where both species experienced a strong barrier to gene flow, seemingly due to lack of suitable habitat. Our findings verify expectations that a fragmented habitat and absence of a pelagic larval stage promote genetic structure, while presence of a pelagic larvae stage increases demographic connectivity and gene flow, except perhaps over extensive habitat gaps.

Population genomics of Monadenia (Gastropoda: Stylommatophora: Xanthonychidae) land snails reveals structuring but gene-flow across distinct species and morphotypes - Jessica A. Oswald; Barry Roth; Trevor M. Faske; Julie M. Allen; Cathleen Mestre; Darci Rivers-Pankratz; Kelli Van Norman; Robert P. Guralnick (Conservation Genetics, 2022)

Measuring circulating triglycerides in free-living birds: evaluation of a field-usable point-of-care analyzer for American woodcock - Christopher M. Roelandt; Amber M. Roth; Scott R. McWilliams; Jill C. Witt (Journal of Ornithology, 2022)

Role of ingesta particle size in the green turtle grazing strategy, ontogenetic diet shifts, and responses to seagrass declines - Alexandra G. Gulick; Anne B. Meylan; Peter A. Meylan; Kristen M. Hart; Jennifer A. Gray; Gaëlle Roth; Alan B. Bolten; Karen A. Bjorndal (Marine Biology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Psychometric utility of the international HIV dementia scale and Montreal Cognitive Assessment in HIV-associated asymptomatic neurocognitive impairment - Stephen L. Aita; Quanhathai Kaewpoowat; Saowaluck Yasri; Amaraporn Rerkasem; Kittipan Rerkasem; Janejit Choovuthayakorn; Somsanguan Ausayakhun; Kevin Robertson; Robert M. Roth; Nathaniel M. Robbins (Journal of NeuroVirology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Protease Inhibitors, Saquinavir and Darunavir, Inhibit Oligodendrocyte Maturation: Implications for Lysosomal Stress - Lindsay Festa; Lindsay M. Roth; Brigid K. Jensen; Jonathan D. Geiger; Kelly L. Jordan-Sciutto; Judith B. Grinspan (Journal of Neuroimmune Pharmacology, 2021)

Methods for Laser-Induced Fluorescence Imaging of Solute Plumes at the Darcy Scale in Quasi-Two-Dimensional, Refractive Index-Matched Porous Media - Eric J. Roth; David C. Mays; Roseanna M. Neupauer; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2021)

Application and clinical impact of the RESIST-4 O.K.N.V. rapid diagnostic test for carbapenemase detection in blood cultures and clinical samples - Sophie Roth; Fabian K. Berger; Andreas Link; Anna Nimmesgern; Philipp M. Lepper; Niels Murawski; Jörg T. Bittenbring; Sören L. Becker (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Invasive infections caused by carbapenemase-producing bacteria are associated with excess mortality. We applied a rapid diagnostic test (RDT) on clinical samples with an elevated likelihood of carbapenemase-producing bacteria and documented its impact on antibiotic treatment decisions. Among 38 patients, twelve tested positive for infections caused by carbapenemase-producing bacteria (31.6%), mainly in blood cultures. KPC ( n = 10) was more frequent than OXA-48 ( n = 2). RDT-based carbapenemase detection led to a treatment modification to ceftazidime/avibactam-containing regimens in all patients before detailed antibiotic testing results became available. Eleven patients (92%) survived the acute infection, whereas one patient with a ceftazidime/avibactam- and colistin-resistant OXA-48-positive isolate died.

High summer temperatures amplify functional differences between coral‐ and algae‐dominated reef communities - Florian Roth; Nils RAdecker; Susana Carvalho; Carlos M. Duarte; Vincent Saderne; Andrea Anton; Luis Silva; Maria Ll. Calleja; XosÉ Anxelu G. MorÁn; Christian R. Voolstra; Benjamin Kürten; Burton H. Jones; et al. (Ecology, 2021)
Shifts from coral to algal dominance are expected to increase in tropical coral reefs as a result of anthropogenic disturbances. The consequences for key ecosystem functions such as primary productivity, calcification, and nutrient recycling are poorly understood, particularly under changing environmental conditions. We used a novel in situ incubation approach to compare functions of coral‐ and algae‐dominated communities in the central Red Sea bimonthly over an entire year. In situ gross and net community primary productivity, calcification, dissolved organic carbon fluxes, dissolved inorganic nitrogen fluxes, and their respective activation energies were quantified to describe the effects of seasonal changes. Overall, coral‐dominated communities exhibited 30% lower net productivity and 10 times higher calcification than algae‐dominated communities. Estimated activation energies indicated a higher thermal sensitivity of coral‐dominated communities. In these communities, net productivity and calcification were negatively correlated with temperature (>40% and >65% reduction, respectively, with +5°C increase from winter to summer), whereas carbon losses via respiration and dissolved organic carbon release more than doubled at higher temperatures. In contrast, algae‐dominated communities doubled net productivity in summer, while calcification and dissolved organic carbon fluxes were unaffected. These results suggest pronounced changes in community functioning associated with coral‐algal phase shifts. Algae‐dominated communities may outcompete coral‐dominated communities because of their higher productivity and carbon retention to support fast biomass accumulation while compromising the formation of important reef framework structures. Higher temperatures likely amplify these functional differences, indicating a high vulnerability of ecosystem functions of coral‐dominated communities to temperatures even below coral bleaching thresholds. Our results suggest that ocean warming may not only cause but also amplify coral–algal phase shifts in coral reefs.

Typologies of individuals vulnerable to insomnia: a two-step cluster analysis - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; Christopher L. Drake; Thomas Roth; Charles M. Morin; Maria Helena Pinto de Azevedo (Sleep and Biological Rhythms, 2021)

Modeling the Supporting Ecosystem Services of Depressional Wetlands in Agricultural Landscapes - David M. Mushet; Cali L. Roth (Wetlands, 2020)
We explored how a geographic information system modeling approach could be used to quantify supporting ecosystem services related to the type, abundance, and distribution of landscape components. Specifically, we use the Integrated Valuation of Ecosystem Services and Tradeoffs model to quantify habitats that support amphibians and birds, floral resources that support pollinators, native-plant communities that support regional biodiversity, and above- and below-ground carbon stores in the Des Moines Lobe ecoregion of the U.S. We quantified services under two scenarios, one that represented the 2012 Des Moines Lobe landscape, and one that simulated the conversion to crop production of wetlands and surrounding uplands conserved under the USDA Agricultural Conservation Easement Program (ACEP). While ACEP easements only covered 0.35% of the ecoregion, preserved wetlands and grasslands provided for 19,020 ha of amphibian habitat, 21,462 ha of grassland-bird habitat, 18,798 ha of high-quality native wetland plants, and 27,882 ha of floral resources for pollinators. Additionally, ACEP protected lands stored 257,722 t of carbon that, if released, would result in costs in excess of 45-million USD. An integrated approach using results from a GIS-based model in combination with process-based model quantifications will facilitate more informed decisions related to ecosystem service tradeoffs.

Zoo visitors affect sleep, displacement activities, and affiliative and aggressive behaviors in captive ebony langurs (Trachypithecus auratus) - Allison M. Roth; Marina Cords (acta ethologica, 2020)

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Wall Effect Mitigation Techniques for Experiments with Planar Walls - Eric J. Roth; Roseanna M. Neupauer; David C. Mays; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2020)

Concurrent isolation of hepatic stem cells and hepatocytes from the human liver - Serene M. L. Lee; Cristina Bertinetti-Lapatki; Tobias S. Schiergens; Karl-Walter Jauch; Adrian B. Roth; Wolfgang E. Thasler (In Vitro Cellular & Developmental Biology - Animal, 2020)
Hepatocytes differentiated from induced pluripotent stem cells or stem cells have the potential to be representative in vitro models of the human liver for research as well as early safety assessment programs. However, up until now, there has been no definitive proof that differentiated hepatocytes recapitulate the phenotype and functional characteristics of primary hepatocytes from the same individual. Thus, a method for the concurrent isolation of hepatocytes and hepatic stem cells is presented here to provide the cells necessary for the evaluation of the required benchmarking. The method presented here generated high-quality hepatocytes with a purity of 94 ± 1% and a high percentage viability of 79 ± 2%. Furthermore, the hepatic stem cells isolated were found to be actively proliferating and have a purity of 98 ± 1%. Thus, these isolated cells can be used as a powerful tool for the validation of differentiated hepatocyte in vitro models.

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Parasitic Personalities: Consistent Individual Differences in Behavior in a Facultatively Parasitic Mite - Emily S. Durkin; Allison M. Roth; Carl N. Keiser (Journal of Insect Behavior, 2020)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Constraints to the capacity of smallholder farming households to adapt to climate change in South and Southeast Asia - Peter R. Brown; Sharmin Afroz; Lytoua Chialue; T. Chiranjeevi; Sotheary El; Clemens M. Grünbühel; Iqbal Khan; Cathy Pitkin; V. Ratna Reddy; Christian H. Roth; Silinthone Sacklokham; Liana J. Williams (Climate and Development, 2019)

Changes in the distribution of Michigan crayfishes and the influence of invasive rusty crayfish (Faxonius rusticus) on native crayfish substrate associations - Kelley R. Smith; Brian M. Roth; Michael L. Jones; Daniel B. Hayes; Seth J. Herbst; Nicholas Popoff (Biological Invasions, 2019)

The diversity of saproxylic insects (Coleoptera, Heteroptera) on four tree species of the Hyrcanian forest in Iran - Jörg Müller; Hassan Barimani Varandi; Mohammad Reza Babaii; Mohammad Ebrahim Farashiani; Khosro Sageb-Talebi; Frank Lange; Martin M. Gossner; Andrea Jarzabek-Müller; Nicolas Roth; Simon Thorn; Sebastian Seibold (Journal of Insect Conservation, 2018)

Testing the ‘plant domestication-reduced defense’ hypothesis in blueberries: the role of herbivore identity - Johnattan Hernandez-Cumplido; M. Monica Giusti; Yucheng Zhou; Vera Kyryczenko-Roth; Yolanda H. Chen; Cesar Rodriguez-Saona (Arthropod-Plant Interactions, 2018)

A Prospective Study of Humoral and Cellular Immune Responses to Hepatitis B Vaccination in Habitual Marijuana Smokers - Sylvia M. Kiertscher; Pallavi R. Gangalum; Grace Ibrahim; Donald P. Tashkin; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2018)

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure - M. J. Ruggiero; K. E. Boschen; T. L. Roth; A. Y. Klintsova (Journal of Neuroimmune Pharmacology, 2018)

Characterization of a newly isolated freshwater Eustigmatophyte alga capable of utilizing far-red light as its sole light source - Benjamin M. Wolf; Dariusz M. Niedzwiedzki; Nikki Cecil M. Magdaong; Robyn Roth; Ursula Goodenough; Robert E. Blankenship (Photosynthesis Research, 2018)

Airflow Simulations in Infant, Child, and Adult Pulmonary Conducting Airways - Jessica M. Oakes; Steven C. Roth; Shawn C. Shadden (Annals of Biomedical Engineering, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Quantitative biogeography of picoprasinophytes establishes ecotype distributions and significant contributions to marine phytoplankton - Alexander J. Limardo; Sebastian Sudek; Chang Jae Choi; Camille Poirier; Yoshimi M. Rii; Marguerite Blum; Robyn Roth; Ursula Goodenough; Matthew J. Church; Alexandra Z. Worden (Environmental Microbiology, 2017)
Summary Bathycoccus and Ostreococcus are broadly distributed marine picoprasinophyte algae. We enumerated small phytoplankton using flow cytometry and qPCR assays for phylogenetically distinct Bathycoccus clades BI and BII and Ostreococcus clades OI and OII. Among 259 photic‐zone samples from transects and time‐series, Ostreococcus maxima occurred in the North Pacific coastal upwelling for OI (36 713 ± 1485 copies ml −1 ) and the Kuroshio Front for OII (50 189 ± 561 copies ml −1 ) and the two overlapped only in frontal regions. The Bathycoccus overlapped more often with maxima along Line‐P for BI (10 667 ± 1299 copies ml −1 ) and the tropical Atlantic for BII (4125 ± 339 copies ml −1 ). Only BII and OII were detected at warm oligotrophic sites, accounting for 34 ± 13% of 1589 ± 448 eukaryotic phytoplankton cells ml −1 (annual average) at Station ALOHA's deep chlorophyll maximum. Significant distributional and molecular differences lead us to propose that Bathycoccus clade BII represents a separate species which tolerates higher temperature oceanic conditions than Bathycoccus prasinos (BI). Morphological differences were not evident, but quick‐freeze deep‐etch electron microscopy provided insight into Bathycoccus scale formation. Our results highlight the importance of quantitative seasonal abundance data for inferring ecological distributions and demonstrate significant, differential picoprasinophyte contributions in mesotrophic and open‐ocean waters.

Clinical profile of suvorexant for the treatment of insomnia over 3 months in women and men: subgroup analysis of pooled phase-3 data - W. Joseph Herring; Kathryn M. Connor; Ellen Snyder; Duane B. Snavely; Ying Zhang; Jill Hutzelmann; Deborah Matzura-Wolfe; Ruth M. Benca; Andrew D. Krystal; James K. Walsh; Christopher Lines; Thomas Roth; et al. (Psychopharmacology, 2017)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

A novel forest state assessment methodology to support conservation and forest management planning - T. Standovár; F. Szmorad; B. Kovács; K. Kelemen; M. Plattner; T. Roth; Zs. Pataki (Community Ecology, 2016)

Household types as a tool to understand adaptive capacity: case studies from Cambodia, Lao PDR, Bangladesh and India - Liana J. Williams; Sharmin Afroz; Peter R. Brown; Lytoua Chialue; Clemens M. Grünbühel; Tanya Jakimow; Iqbal Khan; Mao Minea; V. Ratna Reddy; Silinthone Sacklokham; Emmanuel Santoyo Rio; Mak Soeun; et al. (Climate and Development, 2016)

Recommendations for Capacity Development in Water Resources Engineering and Environmental Management in Latin America - Helge Bormann; Jürgen Steinbrecher; Ingrid Althoff; Hubert Roth; Julian Baez; Carlos Frank; Mariana Gonzalez; Carlos Huenchuleo; Lisa Lugo; Ricardo Mata; Manuela M. Portela; José M. Reichert; et al. (Water Resources Management, 2016)

Assessing vulnerability: an integrated approach for mapping adaptive capacity, sensitivity, and exposure - Shawn W. Margles Weis; Vera N. Agostini; Lynnette M. Roth; Ben Gilmer; Steven R. Schill; John English Knowles; Ruth Blyther (Climatic Change, 2016)

Siderophore production by streptomycetes—stability and alteration of ferrihydroxamates in heavy metal-contaminated soil - Eileen Schütze; Engy Ahmed; Annekatrin Voit; Michael Klose; Matthias Greyer; Aleš Svatoš; Dirk Merten; Martin Roth; Sara J. M. Holmström; Erika Kothe (Environmental Science and Pollution Research, 2015)

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

Applicability of APSIM to capture the effectiveness of irrigation management decisions in rice-based cropping sequence in the Upper-Gangetic Plains of India - N. Subash; M. Shamim; V. K. Singh; B. Gangwar; B. Singh; D. S. Gaydon; C. H. Roth; P. L. Poulton; A. K. Sikka (Paddy and Water Environment, 2015)

Sustainability of Corn Stover Harvest Strategies in Pennsylvania - Paul R. Adler; Benjamin M. Rau; Gregory W. Roth (BioEnergy Research, 2015)

Absence of hybridisation between Fuscospora species at a site in Arthur's Pass National Park, New Zealand - RD Smissen; C Mitchell; M Roth; PB Heenan (New Zealand Journal of Botany, 2015)
We analysed simple sequence repeat markers for a selection of red beech ( Fuscospora fusca ) and mountain beech ( Fuscospora cliffortioides ) trees growing together and for seeds collected from them. Our analysis detected neither hybrid trees nor hybrid seeds within our sample. We suggest pre‐zygotic reproductive isolating mechanisms such as differences in flowering time may be important in maintaining boundaries between Fuscospora species despite extensive sympatry.

Exposure to Δ9-Tetrahydrocannabinol Impairs the Differentiation of Human Monocyte-derived Dendritic Cells and their Capacity for T cell Activation - Michael D. Roth; Julie T. Castaneda; Sylvia M. Kiertscher (Journal of Neuroimmune Pharmacology, 2015)

Invasive earthworms interact with abiotic conditions to influence the invasion of common buckthorn (Rhamnus cathartica) - Alexander M. Roth; Timothy J. S. Whitfeld; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Oecologia, 2015)

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

Developing a common currency for stable isotope analyses of nesting marine turtles - Simona A. Ceriani; James D. Roth; Llewellyn M. Ehrhart; Pedro F. Quintana-Ascencio; John F. Weishampel (Marine Biology, 2014)

Resident plant diversity and introduced earthworms have contrasting effects on the success of invasive plants - Timothy J. S. Whitfeld; Alexander M. Roth; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Biological Invasions, 2014)

Critical role for peripherally-derived interleukin-10 in mediating the thermoregulatory manifestations of fever and hypothermia in severe forms of lipopolysaccharide-induced inflammation - Lois M. Harden; Christoph Rummel; Helen P. Laburn; Jelena Damm; Florian Wiegand; Stephen Poole; Rüdiger Gerstberger; Joachim Roth (Pflügers Archiv - European Journal of Physiology, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Selection of Multiple Umbrella Species for Functional and Taxonomic Diversity to Represent Urban Biodiversity - T. SATTLER; G. B. PEZZATTI; M. P. NOBIS; M. K. OBRIST; T. ROTH; M. MORETTI (Conservation Biology, 2014)
Surrogates, such as umbrella species, are commonly used to reduce the complexity of quantifying biodiversity for conservation purposes. The presence of umbrella species is often indicative of high taxonomic diversity; however, functional diversity is now recognized as an important metric for biodiversity and thus should be considered when choosing umbrella species. We identified umbrella species associated with high taxonomic and functional biodiversity in urban areas in Switzerland. We analyzed 39,752 individuals of 574 animal species from 96 study plots and 1397 presences of 262 plant species from 58 plots. Thirty‐one biodiversity measures of 7 taxonomic groups (plants, spiders, bees, ground beetles, lady bugs, weevils and birds) were included in within‐ and across‐taxa analyses. Sixteen measures were taxonomical (species richness and species diversity), whereas 15 were functional (species traits including mobility, resource use, and reproduction). We used indicator value analysis to identify umbrella species associated with single or multiple biodiversity measures. Many umbrella species were indicators of high biodiversity within their own taxonomic group (from 33.3% in weevils to 93.8% in birds), to a lesser extent they were indicators across taxa. Principal component analysis revealed that umbrella species for multiple measures of biodiversity represented different aspects of biodiversity, especially with respect to measures of taxonomic and functional diversity. Thus, even umbrella species for multiple measures of biodiversity were complementary in the biodiversity aspects they represented. Thus, the choice of umbrella species based solely on taxonomic diversity is questionable and may not represent biodiversity comprehensively. Our results suggest that, depending on conservation priorities, managers should choose multiple and complementary umbrella species to assess the state of biodiversity. Selección de Múltiples Especies Paraguas para la Diversidad Funcional y Taxonómica para Representar la Biodiversidad Urbana

Neonatal steroids induce a down-regulation of tenascin-C and elastin and cause a deceleration of the first phase and an acceleration of the second phase of lung alveolarization - Matthias Roth-Kleiner; Thomas M. Berger; Sandrine Gremlich; Stefan A. Tschanz; Sonja I. Mund; Martin Post; Marco Stampanoni; Johannes C. Schittny (Histochemistry and Cell Biology, 2014)

Predator detection and dilution as benefits of associations between yellow mongooses and Cape ground squirrels - Sarah A. Makenbach; Jane M. Waterman; James D. Roth (Behavioral Ecology and Sociobiology, 2013)

Microhabitat heterogeneity in temperate forests: is distance to stems affecting ground-dwelling spider communities? - T. Ziesche; M. Roth (Community Ecology, 2013)

Differential Expression of Intracellular and Extracellular CB2 Cannabinoid Receptor Protein by Human Peripheral Blood Leukocytes - Julie T. Castaneda; Airi Harui; Sylvia M. Kiertscher; Jeffrey D. Roth; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2013)

Differential hippocampal gene expression is associated with climate‐related natural variation in memory and the hippocampus in food‐caching chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; R. Kramer; F. Schilkey; A. M. van der Linden (Molecular Ecology, 2013)
There is significant and often heritable variation in cognition and its underlying neural mechanisms, yet specific genetic contributions to such variation are not well characterized. Black‐capped chickadees present a good model to investigate the genetic basis of cognition because they exhibit tremendous climate‐related variation in memory, hippocampal morphology and neurogenesis rates throughout the North American continent, and these cognitive traits appear to have a heritable basis. We examined the hippocampal transcriptome profiles of laboratory‐reared chickadees from the two most divergent populations to test whether differential gene expression in the hippocampus is associated with population differences in spatial memory, hippocampal morphology and adult hippocampal neurogenesis rates. Using high‐resolution mRNA sequencing coupled to a de novo transcriptome assembly, we generated 23 295 consensus sequences, which predicted 16 206 protein sequences with 13 982 showing high similarity to known protein sequences or conserved hypothetical proteins in other species. Of these, we identified differential expression in nearly 380 genes, with 47 genes specifically linked to neurogenesis, apoptosis, synaptic function, and learning and memory processes. Many of the other differentially expressed genes, however, may be associated with other functions. Our study presents the first avian hippocampal transcriptome, and it is the first study identifying differential gene expression associated with natural variation in cognition and the hippocampus. Our results provide additional support to the hypothesis that population differences in memory, hippocampal morphology and neurogenesis in chickadees have likely resulted from natural selection that appears to act on memory and its underlying neural mechanisms.

How Effective is Reduced Tillage–Cover Crop Management in Reducing N2O Fluxes from Arable Crop Soils? - M. Abdalla; K. Rueangritsarakul; M. Jones; B. Osborne; M. Helmy; B. Roth; J. Burke; P. Nolan; P. Smith; M. Williams (Water, Air, & Soil Pollution, 2012)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Population genetic structure and its implications for adaptive variation in memory and the hippocampus on a continental scale in food‐caching black‐capped chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; T. M. Burg; M. J. Braun; B. S. Davidson (Molecular Ecology, 2012)
Food‐caching birds rely on stored food to survive the winter, and spatial memory has been shown to be critical in successful cache recovery. Both spatial memory and the hippocampus, an area of the brain involved in spatial memory, exhibit significant geographic variation linked to climate‐based environmental harshness and the potential reliance on food caches for survival. Such geographic variation has been suggested to have a heritable basis associated with differential selection. Here, we ask whether population genetic differentiation and potential isolation among multiple populations of food‐caching black‐capped chickadees is associated with differences in memory and hippocampal morphology by exploring population genetic structure within and among groups of populations that are divergent to different degrees in hippocampal morphology. Using mitochondrial DNA and 583 AFLP loci, we found that population divergence in hippocampal morphology is not significantly associated with neutral genetic divergence or geographic distance, but instead is significantly associated with differences in winter climate. These results are consistent with variation in a history of natural selection on memory and hippocampal morphology that creates and maintains differences in these traits regardless of population genetic structure and likely associated gene flow.

Isoform specific regulation of divalent metal (ion) transporter (DMT1) by proteasomal degradation - Michael D. Garrick; Lin Zhao; Jerome A. Roth; Houbo Jiang; Jian Feng; Natalie J. Foot; Hazel Dalton; Sharad Kumar; Laura M. Garrick (BioMetals, 2012)

Comparison of the novel ResPlex III assay and existing techniques for the detection and subtyping of influenza virus during the influenza season 2006–2007 - M. Eggers; B. Roth; B. Schweiger; M. Schmid; J.-P. Gregersen; M. Enders (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Leaf Surface Wettability and Implications for Drop Shedding and Evaporation from Forest Canopies - W. Konrad; M. Ebner; C. Traiser; A. Roth-Nebelsick (Pure and Applied Geophysics, 2012)

Lack of ceruloplasmin expression alters aspects of copper transport to the fetus and newborn, as determined in mice - Yu-Ling Chu; Eric N. Sauble; Anthony Cabrera; Aleeza Roth; M. Leigh Ackland; Julian F. B. Mercer; Maria C. Linder (BioMetals, 2012)

Locomotor adaptation to resistance during treadmill training transfers to overground walking in human SCI - Sheng-Che Yen; Brian D. Schmit; Jill M. Landry; Heidi Roth; Ming Wu (Experimental Brain Research, 2012)

Does insulin-like growth factor 1 genotype influence muscle power response to strength training in older men and women? - Suchi Sood; Erik D. Hanson; Matthew J. Delmonico; Matthew C. Kostek; Brian D. Hand; Stephen M. Roth; Ben F. Hurley (European Journal of Applied Physiology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning - John C. Dreixler; Ajay Sampat; Afzhal R. Shaikh; Michael Alexander; Marcus M. Marcet; Steven Roth (Journal of Molecular Neuroscience, 2011)

Porous EH and EH-PEG Scaffolds as Gene Delivery Vehicles to Skeletal Muscle - Erin E. Falco; Martha O. Wang; Joshua A. Thompson; Joshua M. Chetta; Diana M. Yoon; Erik Z. Li; Mangesh M. Kulkami; Sameer Shah; Abhay Pandit; J. Scott Roth; John P. Fisher (Pharmaceutical Research, 2011)

Mathematical modeling to distinguish cell cycle arrest and cell killing in chemotherapeutic concentration response curves - Salaheldin S. Hamed; Charles M. Roth (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Reconstitution of huPBL-NSG Mice with Donor-Matched Dendritic Cells Enables Antigen-Specific T-cell Activation - Airi Harui; Sylvia M. Kiertscher; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2011)

ICUC‐7 Urban Climate Special Issue - M. Roth; R. Emmanuel; T. Ichinose; J. Salmond (International Journal of Climatology, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

The armadillo repeat domain of Apc suppresses intestinal tumorigenesis - Richard C. Crist; Jacquelyn J. Roth; Amy A. Baran; Benjamin J. McEntee; Linda D. Siracusa; Arthur M. Buchberg (Mammalian Genome, 2010)

A simulation of food‐web interactions leading to rainbow smelt Osmerus mordax dominance in Sparkling Lake, Wisconsin - B. M. Roth; T. R. Hrabik; C. T. Solomon; N. Mercado‐Silva; J. F. Kitchell (Journal of Fish Biology, 2010)
A process‐based simulation model was used to examine the nature and intensity of food‐web interactions that allow Osmerus mordax to dominate invaded lakes. The model simulates food‐web interactions among linked populations of O. mordax , Coregonus artedi and Sander vitreus . Simulations indicated that O. mordax dominate where: (1) adult O. mordax prey on young‐of‐the‐year (YOY) C. artedi , (2) YOY O. mordax negatively affect YOY S. vitreus through competition and (3) adult S. vitreus experience moderate fishing mortality. Osmerus mordax dominated simulations across a broad range of variable values that regulated competition and predation, and displayed threshold responses to increasing angler harvest. Consequently, angler harvest should be carefully managed in lakes susceptible to O. mordax invasions because the alternative could lead to fishery collapse.

Role of kappa-opioid receptors in the effects of salvinorin A and ketamine on attention in rats - Christina L. Nemeth; Tracie A. Paine; Joseph E. Rittiner; Cécile Béguin; F. Ivy Carroll; Bryan L. Roth; Bruce M. Cohen; William A. Carlezon (Psychopharmacology, 2010)

RNase 1 genes from the family Sciuridae define a novel rodent ribonuclease cluster - Steven J. Siegel; Caroline M. Percopo; Kimberly D. Dyer; Wei Zhao; V. Louise Roth; John M. Mercer; Helene F. Rosenberg (Mammalian Genome, 2009)

Short-Term Effects of an Oil Spill on Marsh-Edge Fishes and Decapod Crustaceans - Agatha-Marie F. Roth; Donald M. Baltz (Estuaries and Coasts, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Trial-to-trial size variability of motor-evoked potentials. A study using the triple stimulation technique - Kai M. Rösler; Denise M. Roth; Michel R. Magistris (Experimental Brain Research, 2008)

Complex Microsatellite Dynamics in the Myostatin Gene Within Ruminants - Åsa Tellgren-Roth; Grigory Kolesov; Ana M. Sifuentes-Rincón; David A. Liberles (Journal of Molecular Evolution, 2008)

Is the age of forest habitats affecting the reproductive rate of generalist predatory ground beetle species? - T. Ziesche; M. Roth (Community Ecology, 2007)

Urban Climatology ICUC6 - C. S. B. Grimmond; W. Kuttler; S. Lindqvist; M. Roth (International Journal of Climatology, 2007)

Mercury and Organic Carbon Dynamics During Runoff Episodes from a Northeastern USA Watershed - P. F. Schuster; J. B. Shanley; M. Marvin-Dipasquale; M. M. Reddy; G. R. Aiken; D. A. Roth; H. E. Taylor; D. P. Krabbenhoft; J. F. DeWild (Water, Air, & Soil Pollution, 2007)

Interspecific associations of Cape ground squirrels with two mongoose species: benefit or cost? - Jane M. Waterman; James D. Roth (Behavioral Ecology and Sociobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Preserved dynamic cerebral autoregulation in the middle cerebral artery among persons with migraine - M. Reinhard; E. Wehrle-Wieland; M. Roth; W. D. Niesen; J. Timmer; C. Weiller; A. Hetzel (Experimental Brain Research, 2007)

Microglial Activation is Required for Aβ Clearance After Intracranial Injection of Lipopolysaccharide in APP Transgenic Mice - Donna L. Herber; Mary Mercer; Lisa M. Roth; Keisha Symmonds; Jessica Maloney; Nedda Wilson; Melissa J. Freeman; Dave Morgan; Marcia N. Gordon (Journal of Neuroimmune Pharmacology, 2007)

Coupling of groundwater and surface water at Lake Willersinnweiher: Groundwater modeling and tracer studies - Ute Wollschläger; Johann Ilmberger; Margot Isenbeck-Schröter; Andreas M. Kreuzer; Christoph von Rohden; Kurt Roth; Wolfgang Schäfer (Aquatic Sciences, 2007)

Reciprocal Relationships Between Exotic Rusty Crayfish, Macrophytes, and Lepomis Species in Northern Wisconsin Lakes - Brian M. Roth; Jakob C. Tetzlaff; Mara L. Alexander; James F. Kitchell (Ecosystems, 2007)

Budesonide effects on Clara cell under normal and allergic inflammatory condition - Felix Daniel Roth; Amado Alfredo Quintar; Elisa M. Uribe Echevarría; Alicia Inés Torres; Agustín Aoki; Cristina Alicia Maldonado (Histochemistry and Cell Biology, 2006)

Dose-dependent retrograde facilitation of verbal memory in healthy elderly after acute oral lorazepam administration - Nunzio Pomara; Thomas M. Facelle; Amy E. Roth; Lisa M. Willoughby; David J. Greenblatt; John J. Sidtis (Psychopharmacology, 2006)

Effect of In Vivo Administration of Ethylmalonic Acid on Energy Metabolism in Rat Tissues - Gustavo da C. Ferreira; Karina Roth André; Patrícia Fernanda Schuck; Carolina M. Viegas; Anelise Tonin; Daniella de Moura Coelho; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Moacir Wajner (Metabolic Brain Disease, 2006)

Computer Technology Helps Family Forest Owners in Pennsylvania and Washington - Paul A. Roth; James C. Finley; Kevin W. Zobrist; David M. Baumgartner (Journal of Forestry, 2006)
The use of computer technology in managing family forestlands is increasing. Growth, treatment, and visualization models can facilitate better understanding and communication of sustainable forest management concepts. Learning to use these tools can be challenging, and the technology has not been widely adopted at the landowner level. The Landscape Management System and associated Inventory Wizard have made these technologies easier to use and more accessible to landowners. Programs in Pennsylvania and Washington are promoting the use of this system by family forest owners.

Seasonal cycle in vitamin A1/A2-based visual pigment composition during the life history of coho salmon (Oncorhynchus kisutch) - S. E. Temple; E. M. Plate; S. Ramsden; T. J. Haimberger; W.-M. Roth; C. W. Hawryshyn (Journal of Comparative Physiology A, 2006)

Temporal dynamics of CO2 fluxes and profiles over a Central European city - R. Vogt; A. Christen; M. W. Rotach; M. Roth; A. N. V. Satyanarayana (Theoretical and Applied Climatology, 2006)

Analysis of mycorrhizal associations formed by Cistus incanus transformed root clones with Terfezia boudieri isolates - M. Zaretsky; V. Kagan-Zur; D. Mills; N. Roth-Bejerano (Plant Cell Reports, 2006)

X-ray powder diffraction and 57Fe – Mössbauer spectroscopy of synthetic trioctahedral micas K[Me3] $\langle$ TSi3 $\rangle$ O10(OH)2, Me = Ni2+, Mg2+, Co2+, Fe2+; T = Al3+, Fe3+ - G. J. Redhammer; G. Amthauer; W. Lottermoser; M. Bernroider; G. Tippelt; G. Roth (Mineralogy and Petrology, 2005)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

Growth temperature affects accumulation of exogenous fatty acids and fatty acid composition in Schizosaccharomyces pombe - Virginia M. McDonough; Therese M. Roth (Antonie van Leeuwenhoek, 2005)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Relationship Between Territorial Male Golden-Winged Warblers in Managed Aspen Stands in Northern Wisconsin, USA - Amber M. Roth; Scott Lutz (Forest Science, 2004)
We compared territorial male Golden-winged Warbler (Vermivora chrysoptera) (GWWA) density and territory placement across four size classes [(1) seedling (<2.5 cm mean diameter at breast height (dbh)), (2) small sapling (3.0–6.0 cm dbh), (3) large sapling (7.0–11.5 cm dbh), (4) pole (12.5–17.0 cm dbh)] of aspen forests (Populus spp.) in northern Wisconsin. We surveyed four stands in each size class in May-June 2000 and observed the highest male density (0.55 males/ha) in the seedling size class. Male density for size classes 2–4 combined was 0.04 males/ha. Aspen sucker density was a good predictor of male density across size classes and thus may be a good indicator of habitat quality in aspen communities. Mean GWWA territory area was 0.82 ha (n = 12) in Size Class 1, 0.54 ha (n = 6) in Size Class 4, and 0.18 ha (n = 6) for Size Classes 2 and 3 combined. We found no relationship between male density and the amount of stand edge (km/ha), and territories did not consistently include the stand edge. Because GWWA are strongly associated with aspen seedling stem densities and this aspen stand size class is suitable to GWWAs for a relatively short period of time, we believe conservation will require managing aspen forests to ensure that habitat is always available. Clearcutting aspen forest is a practical strategy to create GWWA breeding cover in the Upper Great Lakes Region. FOR. SCI. 50(2):153–161.

Examination of Physical and Regulatory Variables Leading to Small Dam Removal in Wisconsin - Cailin H. Orr; Brian M. Roth; Kenneth J. Forshay; James D. Gonzales; Michael M. Papenfus; Rebecca D.G. Wassell (Environmental Management, 2004)

Growth temperature affects accumulation of exogenous fatty acids and fatty acid composition in Schizosaccharomyces pombe - Virginia M. McDonough; Therese M. Roth (Antonie van Leeuwenhoek, 2004)

Water flow and solute transport in furrow-irrigated fields - Fariborz Abbasi; Jan Feyen; Robert L. Roth; Mike Sheedy; M. T. van Genuchten (Irrigation Science, 2003)

Using Environmental Stressor Information to Predict the Ecological Status of Maryland Non-tidal Streams as Measured by Biological Indicators - J. H. Vølstad; N. E. Roth; G. Mercurio; M. T. Southerland; D. E. Strebel (Environmental Monitoring and Assessment, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Differences in chondroitin AC lyase activity of Flavobacterium columnare isolates - K M Stringer‐Roth; W Yunghans; L F Caslake (Journal of Fish Diseases, 2002)

Muscle biopsy and muscle fiber hypercontraction: a brief review - Stephen M. Roth; Gregory F. Martel; Marc A. Rogers (European Journal of Applied Physiology, 2000)

Optomotor and neuropsychological performance in old age - C. Klein; B. Fischer; K. Hartnegg; W. H. Heiss; M. Roth (Experimental Brain Research, 2000)

Carbon mineralization and microbial activity in a field site trial used for 14 C turnover experiments over a period of 30 years - M. Stemmer; K. Roth; E. Kandeler (Biology and Fertility of Soils, 2000)

Acquisition of oral phencyclidine self-administration in rhesus monkeys: effect of sex - M. E. Carroll; M. E. Roth; R. K. Voeller; P. D. Nguyen (Psychopharmacology, 2000)

Comparison of either norepinephrine-uptake inhibitors or phentermine combined with serotonergic agents on food intake in rats - N. E. Rowland; M. Marshall; J. D. Roth (Psychopharmacology, 2000)

The production of polyhydroxybutyrate by Methylobacterium rhodesianum and Ralstonia eutropha in media containing glycerol and casein hydrolysates - E.J. Bormann; M. Roth (Biotechnology Letters, 1999)

Geostrophic Wind, Gradient Wind, Thermal Wind And The Vertical Wind Profile – A Sample Analysis Within A Planetary Boundary Layer Over Arctic Sea-Ice - R. Roth; M. Hofmann; C. Wode (Boundary-Layer Meteorology, 1999)

Interaction of cholera toxin and Escherichia coli heat-labile enterotoxin with glycoconjugates from rabbit intestinal brush border membranes: Relationship with ABH blood group determinants - Luis E. Balanzino; José L. Barra; Estela M. Galváin; German A. Roth; Clara G. Monferran (Molecular and Cellular Biochemistry, 1999)

A “Geographic Information Systems” Based Technique for the Study of Microvascular Networks - Noah M. Roth; Mohammad F. Kiani (Annals of Biomedical Engineering, 1999)

Improved mRNA in situ hybridization on formaldehyde-fixed and paraffin-embedded tissue using signal amplification with different haptenized tyramides - E. J. M. Speel; Parvin Saremaslani; Jürgen Roth; Anton H. N. Hopman; Paul Komminoth (Histochemistry and Cell Biology, 1998)

Aerodynamic Roughness of Urban Areas Derived from Wind Observations - C.S.B. Grimmond; T. S. King; M. Roth; T. R. Oke (Boundary-Layer Meteorology, 1998)

Endocytic routes to the Golgi apparatus - M. Pavelka; Adolf Ellinger; Paul Debbage; Christian Loewe; Monika Vetterlein; Jürgen Roth (Histochemistry and Cell Biology, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

Maryland Biological Stream Survey: A State Agency Program to Assess the Impact of Anthropogenic Stresses on Stream Habitat Quality and Biota - R. Klauda; P. Kazyak; S. Stranko; M. Southerland; N. Roth; J. Chaillou (Environmental Monitoring and Assessment, 1998)

Absence of the hemochromatosis gene Cys282Tyr mutation in three ethnic groups from Algeria (Mzab), Ethiopia, and Senegal - M.-P. Roth; Pilar Giraldo; Ghania Hariti; Estella S. Poloni; Alicia Sanchez-Mazas; Gian Franco De Stefano; Jean-Michel Dugoujon; Hélène Coppin (Immunogenetics, 1997)

Mutations in the MHC class I-like candidate gene for hemochromatosis in French patients - Nicolas Borot; M.-P. Roth; Laurence Malfroy; Chantal Demangel; Jean-Pierre Vinel; Jean-Pierre Pascal; Hélène Coppin (Immunogenetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Magnetic stimulation of axons in a nerve bundle: Effects of current redistribution in the bundle - Srikantan S. Nagarajan; Dominique M. Durand; Brandley J. Roth; Ranjith S. Wijesinghe (Annals of Biomedical Engineering, 1995)

A theoretical comparison of electric and magnetic stimulation of the brain - J. M. Saypol; B. J. Roth; L. G. Cohen; M. Hallett (Annals of Biomedical Engineering, 1992)

A theoretical comparison of electric and magnetic stimulation of the brain - Joshua M. Saypol; Bradley J. Roth; Leonardo G. Cohen; Mark Hallett (Annals of Biomedical Engineering, 1991)

Zinc and insulin metabolism - H.-P. Roth; M. Kirchgessner (Biological Trace Element Research, 1981)

Percutaneous implant devices - Vert Mooney; S. Andrew Schwartz; Andrew M. Roth; Michael J. Gorniowsky (Annals of Biomedical Engineering, 1977)